Dupilumab for the treatment of atopic dermatitis: real-world data from the Czech Republic BIOREP registry - Kojanova, Martina; Česák, Milena; Strosova, Daniela; Cetkovska, Petra; Fialova, Jorga; Dolezal, Tomas; Machovcova, Alena; Gkalpakiotis, Spyridon (Journal of dermatological treatment, 2022)
BACKGROUND: Dupilumab has been approved to treat moderate-to-severe atopic dermatitis; however, the data in a real-world setting are still limited. OBJECTIVE: To analyze the effectiveness and safety of dupilumab. METHODS: This was a real-life Czech multicenter retrospective study from patients treated with dupilumab for severe AD. RESULTS: A total of 360 patients were included. At 16 weeks, 66.6, 34.1, and 5.5% of patients achieved EASI75/90 and EASI100, respectively. Improvement continued with the time, and the proportion of patients with EASI75/90 and EASI100 increased to 89.5, 55.6, and 12.9% after one year of treatment and reached 95.8, 60.4, and 27.1% in the second year of therapy, respectively. A significant reduction was observed in the DLQI scores. The most common adverse events were infections in 5.8% of patients, followed by ocular complications in 2.5% of patients. Persistence rates were 98.2% at four months to 93.1% at month 24, and lack of effectiveness was the most common reason for discontinuation. CONCLUSION: This real-life study confirmed the effectiveness and safety of dupilumab in a real-life setting during the COVID-19 pandemic. Our study revealed a higher frequency of infections and a lower conjunctivitis frequency than other real-life studies and clinical trials.
Keywords: pandemie; COVID-19; retrospektivní studie; Humans; Czech Republic; Dermatitis, Atopic; Registries; Česká republika; Severity of Illness Index; stupeň závažnosti nemoci; humanizované monoklonální protilátky; Antibodies, Monoclonal, Humanized; výsledek terapie; Treatment Outcome; registrace; atopická dermatitida; lidé; Pandemics; Retrospective Studies